Avaliação in vitro e in vivo da atividade imunomoduladora do extrato e frações da inflorescência de Musa paradisiaca L. - Gadelha, Francisco Allysson Assis Ferreira (2024)
Acute lung injury (ALI) is an inflammatory disease with high mortality that affects patients in intensive care and has become a global health problem during the COVID-19 pandemic. Musa paradisiaca L. (banana) is a cosmopolitan plant, and its inflorescence is used in many countries to treat inflammation, however, in Brazil, it is discarded in most cultures. The objective of this study was to evaluate the anti-inflammatory and immunomodulatory activities of the inflorescence extract and its fractions through in vitro and in vivo tests, in the experimental model of ALI induced with lipopolysaccharide (LPS). Optical and immunofluorescence microscopy, flow cytometry, immunoenzymatic and colorimetric assays (ELISA) and histology were used to evaluate anti-inflammatory parameters. The hydroalcoholic extract of Musa (HEM) (100 μg/mL) and its fractions ethyl acetate (FA), n-butanol (FNB), hexane (FH) and dichloromethane (FD) (25 and 50 μg/mL) did not present toxicity in peritoneal macrophages. In in vitro screening, HEM and FA and FH decreased NO production and expression of TLR4 and CD18 receptors. In addition, HEM increased IL-10 production. In in vivo experiments, HEM and FH were evaluated. In animals with ALI treated with HEM, a decrease in migration was observed, mainly of neutrophils in the BALF, in the alveolar region and in the blood, correlating with the decrease in CD18 expression, however, FH (100 mg/kg) did not decrease the migration of cells to the lung cavity as well as edema, cellular infiltration and hemorrhage in the tissue. Treatment with HEM reduced the protein content in BALF, edema, activation of NF-κB dependent on the TLR4 signaling pathway and decreased the production of IL-1β and TNF-α, reduced the amount of free DNA and myeloperoxidase activity (MPO). Corroborating the in vitro findings, treatment with HEM favored the production of IL-10 in BALF. Therefore, the M. paradisiaca inflorescence extract demonstrated anti-inflammatory and immunomodulatory activities in macrophages via decreased NO, increased IL-10 and, in mice with ALI, decreased lung inflammation via TLR4-NF-κB, reduced production of cytokines, as well as the decrease in CD18 expression, release of free DNA and MPO activity. Thus, this study presents scientific data that support the use of banana inflorescences in folk medicine and suggests the development of a pharmaceutical formulation to assist in the treatment of lung inflammation.